Analysis of Expressive Speech Acts in @Folkative Instagram Comment Columns - Putri, Meysi Anisa; Ningsih, Rika (UIR Press, 2025)
This study aims to analyze expressive speech acts in comments on the social media platform Instagram, specifically on the @folkative account. The research employs a qualitative approach with content analysis techniques. Data were collected from comments containing expressive speech acts, which reflect netizens' emotional responses to the published content. The findings reveal five types of expressive speech acts: complaining, praising, congratulating, criticizing, and expressing gratitude. Each type of speech act illustrates the various communication functions that reflect the attitudes and emotions of social media users. This study provides a deeper understanding of how netizens express themselves through comments on digital platforms.